A guide to worker displacement : some tools for reducing the impact on workers, communities and enterprises. Update 2009. - Hansen, Gary B. (International Labour Office, 2009)
This guide is an update to the 2001 Guide to worker displacement that was published as a response to the Asian financial crisis. The Guide, drawing on experience primarily in North America and during the transition process in Central and Eastern Europe, explores how enterprises, communities and workers can respond to the financial crisis and how to reduce potential job losses. This includes possible strategies for averting layoffs and promoting business retention by communities, enterprise managements and workers' association. The guide is primarily for use in industrialized and transition cou.